The relationship of social media marketing, brand awareness and purchase decisions on somethinc products in padang city - Muthiah Dwi Utami; Ratni Prima Lita; Alfitman (Institute of Computer Science (IOCS), 2023)
This study aims to determine the relationship between social media marketing, brand awareness and purchasing decisions for somethinc products in the city of Padang, the population in this study was 150 with a sample of 150 respondents. Data obtained by conducting a questionnaire, then processed and tested using SmartPLS. From the research conducted, it is known that based on the results of hypothesis testing, it is known that directly social media marketing has a significant effect on brand awareness and social media marketing and brand awareness has a significant effect on purchasing decisions. And indirectly brand awareness has a role between social media marketing and purchasing decisions.